Tales of darkness and light : Soso Tham's The old days of the Khasis - Tham, Soso, 1873-1940 (World oral literature series., 2018)
"Soso Tham (1873-1940), the acknowledged poet laureate of the Khasis of northeastern India, was one of the first writers to give written poetic form to the rich oral tradition of his people. Poet of landscape, myth and memory, Soso Tham paid rich and poignant tribute to his tribe in his masterpiece The Old Days of the Khasis. Janet Hujon's vibrant new translation presents the English reader with Tham's long poem, which keeps a rich cultural tradition of the Khasi people alive through its retelling of old narratives and acts as a cultural signpost for their literary identity. This book is essential reading for anyone with an interest in Indian literature and culture and in the interplay between oral traditions and written literary forms. This edition includes: " Original text " English translation " Critical apparatus " Embedded audio recordings of the original text."